2013
DOI: 10.1039/c3tx50022e
|View full text |Cite
|
Sign up to set email alerts
|

Assessing DNA damage from enzyme-oxidized single-walled carbon nanotubes

Abstract: Peroxidase enzyme digests of oxidized single-wall carbon nanotubes (SWCNT) were shown to damage DNA in potentially genotoxic reactions for the first time using an electro-optical array with and without metabolic activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…S6 †). We did not test later time-points because signicant, spontaneous cell death starts to occur in neutrophils aer 6 h. These ndings are in accordance with the recent publication by Pan et al 29 showing that HRP oxidized SWCNTs and their byproducts may yield DNA damage in vitro and in A549 lung carcinoma cells. Notably, Allen et al 11 previously identied oxidized polyaromatic hydrocarbons, well-known tumor inducing agents, following HRP-mediated degradation of SWCNTs.…”
Section: Cytotoxicity Of Partially Degraded Cntssupporting
confidence: 84%
“…S6 †). We did not test later time-points because signicant, spontaneous cell death starts to occur in neutrophils aer 6 h. These ndings are in accordance with the recent publication by Pan et al 29 showing that HRP oxidized SWCNTs and their byproducts may yield DNA damage in vitro and in A549 lung carcinoma cells. Notably, Allen et al 11 previously identied oxidized polyaromatic hydrocarbons, well-known tumor inducing agents, following HRP-mediated degradation of SWCNTs.…”
Section: Cytotoxicity Of Partially Degraded Cntssupporting
confidence: 84%
“…However, these intermediate PAHs may have important toxicological implications (Bai et al, 2014). For example, it has been demonstrated that the oxidation products (e.g., MW < 3000 Da) of horseradish peroxidase-catalyzed degradation of single-wall carbon nanotubes will induce DNA damage (Pan et al, 2013). It was suggested that the products from photoreaction of GO are likely to exhibit different accumulation and toxic properties compared to parent GO (Hou et al, 2015), but the potential toxicological impacts of FLG degraded by the Fenton reaction and its byproducts are not yet well understood.…”
Section: Daphnia Magna Resultsmentioning
confidence: 99%
“… 22 26 In particular, peroxidases such as horseradish peroxidase (HRP), myeloperoxidase, and eosinophil peroxidase have been demonstrated to degrade both carbon nanotubes and graphene oxide. Although the degradation products of myeloperoxidase were shown not to induce toxicity, 23 recently, the oxidation products (e.g., MW < 3000 Da) of HRP-catalyzed degradation of SWCNTs have been identified to induce DNA damage; 27 in that study, however, no structures were identified. Therefore, structural elucidation of the degradation products of carbon nanomaterials represents a relevant and fundamentally important step with implications for diverse fields.…”
Section: Introductionmentioning
confidence: 85%